Therapeutic Potential of a Novel Bifidobacterium Identified Through Microbiome Profiling of RA Patients With Different RF Levels - Jeong, Yunju; Jhun, JooYeon; Lee, Seon-Yeong; Na, Hyun Sik; Choi, JeongWon; Cho, Keun-Hyung; Lee, Seung Yoon; Lee, A Ram; Park, Sang-Jun; You, Hyun Ju; Kim, Ji-Won; Park, Myeong Soo; et al. (Frontiers in Immunology, 2021)
The potential therapeutic effects of probiotic bacteria in rheumatoid arthritis (RA) remain controversial. Thus, this study aimed to discover potential therapeutic bacteria based on the relationship between the gut microbiome and rheumatoid factor (RF) in RA. Bacterial genomic DNA was extracted from the fecal samples of 93 RA patients and 16 healthy subjects. Microbiota profiling was conducted through 16S rRNA sequencing and bioinformatics analyses. The effects of Bifidobacterium strains on human peripheral blood mononuclear cells and collagen-induced arthritis (CIA) mice were assessed. Significant differences in gut microbiota composition were observed in patients with different RF levels. The relative abundance of Bifidobacterium and Collinsella was lower in RF-high than in RF-low and RF-negative RA patients while the relative abundance of Clostridium of Ruminococcaceae family was higher in RF-high than in RF-low and RF-negative patients. Among 10 differentially abundant Bifidobacterium, B. longum RAPO exhibited the strongest ability to inhibit IL-17 secretion. Oral administration of B. longum RAPO in CIA mice, obese CIA and humanized avatar model significantly reduced RA incidence, the arthritis score, inflammation, bone damage, cartilage damage, Th17 cells, and inflammatory cytokine secretion. Additionally, B. longum RAPO significantly inhibited the Th17 cells and th17 related genes-IL-17A, IRF4, RORC, IL-21 and IL-23R in rheumatoid arthritis patients PBMC. Our findings suggest that B. longum RAPO may alleviate RA by inhibiting the production of IL-17 and other proinflammatory mediators. The safety and efficacy of B. longum RAPO in patients with RA and other autoimmune disorders merit further investigation.